Alternative Solutions to Optimalisation of the Gassing-up Operation After Tanks Inerting Using Pressure Swing Adsorption (PSA) and Membrane Techniques - Wieczorek, A. (Scientific Journal of Gdynia Maritime University, 2018)
The article constitutes the introduction to finding a solution to a problemconcerning carrying gassing-up operation in a more efficient way in terms of loosingethylene cargo. To begin with, the impact of nitrogen presence on ethylene cascade cycle’stechnical work and cooling capacity has been described. Further, the results of investigationinto methods of nitrogen removing from cargo tanks after gassing-up have been presented.Possibility of pressure swing adsorption (PSA) and membrane techniques use has beenanalyzed with reference to ethylene carriers.